How Mykola Oleksandrovych Quarrelled With Sergiy Mykhailovych: Kyiv Photographic Exhibitions In The Discourse Of Pictorialism (The Late 19th – Early 20th Cc.) - Казакевич, Геннадій (Київський національний університет імені Тараса Шевченка, 2018)
The paper reveals the history of photographic exhibitions which were held in Kyiv from the mid-19th to the early 20th cc. It demonstrates how Kyiv became one of the most important centres of the artistic photography in the Russian empire. In Kyiv the first photographic exhibition took place in 1867, however, only after the establishment of the Kyiv photographic society “Daguerre” in 1902 the photographic exhibitions became true artistic events holding on the regular basis. As far as the Daguerre society maintained close relations with the Paris photographic club as well as other photographic associations from all over the Europe, a lot of photographers from France, Germany, the United Kingdom and other countries were able to exhibit their works in Kyiv. In particular, the works by famous European and American pictorialists, such as Robert Demachy, Constant Puyo, Rudolf Dührkoop, Alfred Stieglitz, were featured in the exhibitions of 1908 and 1911. Both exhibitions contributed significantly to the promotion of photography in the Russian empire and integration of its amateur photographers into the worldwide artistic community. There were about one hundred members of the Daguerre society. Most of them were amateur photographers who worked as railway engineers in Kyiv and nearby towns. Their creative work was inspired mainly by classical styles of painting, including the Russian realist school, as well as the European pictorial photography. The most prominent member of the Daguerre society was Mykola Petrov who launched teaching of photography in Kyiv Polytechnic institute for the first time the Russian empire. Petrov and his followers strongly supported an ‘artistic’ approach to photography. In 1908-1908 they arranged the International photographic exhibition and All-Russian conference of photographers in Kyiv. The conference approved a resolution, which proclaimed photography as a separate branch of visual art and encouraged organizing committees of photographic exhibitions to accept only the images of significant artistic value. This proclamation caused a negative feedback from the supporters of documentary and scientific photography. Among them was the well-known Russian photographer and chemist Sergey Prokudin-Gorsky. Different views on the goals of photographic exhibitions caused fierce debates between him and Mykola Petrov.

У статті розкрито історію фотографічних виставок, які проводилися у Києві в останній третині ХІХ – на початку ХХ ст. Зазначено, що у цей період Київ став одним з найважливіших центрів художньої фотографії у Російській імперії. Сталося це переважно завдяки діяльності Київського фотографічного товариства «Дагер» та його керівника Миколи Петрова. Важливими подіями мистецького життя Києва початку ХХ ст. стали проведені у місті у 1908 та 1911 роках міжнародні фотографічні виставки, участь в яких взяли провідні європейські фотографи-пікторіалісти, а також Всеросійський з’їзд діячів фотографічної справи. Відстоювання Миколою Петровим підходу до фотографії насамперед як до галузі візуального мистецтва, яке втілилося у резолюції з’їзду, призвело до гострої дискусії між ним та головним редактором журналу «Фотограф-Любитель» Сергієм Прокудіним-Горським.
Як посварився Микола Олекcандрович з Сергієм Михайловичем: київські фотографічні виставки у дискурсі пікторіалізму (кінець ХІХ – початок ХХ ст.)
Keywords: photographic exhibitions; pictorialism; artistic photography; Kyiv photographic society “Daguerre”; Mykola Petrov; Sergey Prokudin-Gorsky; фотографічні виставки; пікторіалізм; художня фотографія; Київське фотографічне товариство «Дагер»; Микола Петров; Сергій Прокудін-Горський